واقع تطبيق عمليات إدارة المعرفة في المكتبات الجامعية " دراسة حالة: مكتبة الكليات الطبية ـــ جامعة بنغازي" - الشيخي , انتصار سعد عبد القادر; الشيخي, أحمد سعد; الشيخي, نورية سعد (Scientific Journal of University of Benghazi, 2022)
The study aimed to identify the level of application of knowledge management processes (acquisition and generation of knowledge, storage of knowledge, dissemination and sharing of knowledge, and application of knowledge) in the Library of Medical Colleges at the University of Benghazi. The primary data was collected using a questionnaire designed for this purpose, and distributed to all employees (29 employees) at the Library of Medical Colleges. The results of the study indicated that the general level of application of knowledge management processes was average. The results of the study also showed that there are statistically significant differences between the averages of the respondents' answers towards knowledge management processes that are attributed to the duration of service in the library under study. The study put forward a set of recommendations, which hopefully will contribute to enhancing the application of knowledge management in the Library of Medical Colleges in particular, and in the libraries of Libyan universities in general.